Numerical Modelling of Seismic Activity at Tabular Orebody Mines in South Africa using the Boundary Element Method - Gerber, Jacques Dewald (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.